Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran - Yousefkhani, Seyyed Saeed Hosseinian; Aliabadian, Mansour; Rastegar-Pouyani, Eskandar; Darvish, Jamshid; Shafiei, Soheila; Sehhatisabet, Mohammad Ebrahim (Zootaxa, 2018)
Herein, we describe a new species of spider gecko, Agamura kermanensis sp. nov., from south Kerman, Iran. The new species is distinguished from other species by having long forelimbs and hindlimbs and a high interorbital distance. Agamura kermanensis sp. nov. was discovered in the Faryab region of southern Kerman Province, which has a xeric climate and low vegetation density. The habitat of the species is similar to that of A. cruralis in southeast Iran. It can be assumed that the distribution of the species is more extensive than currently known. More investigation is required in Jazmourian and the surrounding areas. This is the third species of the genus Agamura discovered on the Iranian Plateau.